Too Much Passion Kills You? The Evidence of Individuals’ Passion in Entrepreneurial Failure - Hafiz Rahman; Eri Besra; Nurhayati Nurhayati (APMBA (Asia Pacific Management and Business Application), 2020)
This paper examines and discusses the presence of individuals’ passion as a psychological construct that may cause entrepreneurial failure – with particular context and analysis to the failed nascent entrepreneurs in one of the largest port city in Sumatera island, Padang, Indonesia. This paper uses quantitative study with relational approach, and was undertaken with 180 failed nascent entrepreneurs in Padang. Data and information were collected by using a questionnaire as a cross-sectional cohort data and were further analyzed with Structural Equation Modelling (SEM) and supported by PLS 3.0 as the statistical tool. Both the process and the content framework were used to show the logic of methodology according to the dualistic model of passion) and their relationship with entrepreneurial failure. The study found that individuals’ harmonious passion in entrepreneurship should also be considered as a cause of entrepreneurial failure, meanwhile the obsessive passion is significantly found to influence entrepreneurial failure. This study implies that entrepreneurs should consider and make clear boundaries between psychological push and rationality when they start new ventures. This paper has value and originality in terms of the examination and analysis of individuals’ passion as a psychological construct that causes entrepreneurial failure. In different with other researches and studies which have merely viewed the passion as a source of entrepreneurial success, this study views and argues that individuals’ passion either is categorized as harmonious or obsessive passions (especially when it is uncontrollable) may also cause the entrepreneurial failure.